1999
DOI: 10.1016/s0002-9440(10)65321-7
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of HLA Class I Antigen-Processing Molecules in Malignant Melanoma

Abstract: Expression of the proteasome subunits LMP2 and LMP7, the MHC-encoded transporter subunits TAP1 and TAP2, and HLA Class I antigens was examined by immunoperoxidase staining in 10 nevi and 98 melanoma lesions (60 primary and 38 metastatic), because these molecules play an important role in the presentation of melanoma-associated peptide antigens to cytotoxic T cells. LMP2 was less frequently expressed than LMP7 in primary and metastatic melanoma lesions. TAP1, TAP2, and HLA Class I antigen expression was more fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
154
3
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 232 publications
(177 citation statements)
references
References 25 publications
14
154
3
6
Order By: Relevance
“…TAP1 down-regulation or loss has been reported in various tumor types at frequencies ranging from 10 to 84%. 6,23 APM defects have been identified in several types of human and mouse tumor, e.g., cervical cancer, 24 cutaneous melanoma, 25 breast cancer, 26 lung cancer, 27 colorectal carcinoma 28 and bladder carcinoma. 29 Down-regulation of APM components may or may not be associated with decreased transcription of HLA class I heavy chain and b2-microglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…TAP1 down-regulation or loss has been reported in various tumor types at frequencies ranging from 10 to 84%. 6,23 APM defects have been identified in several types of human and mouse tumor, e.g., cervical cancer, 24 cutaneous melanoma, 25 breast cancer, 26 lung cancer, 27 colorectal carcinoma 28 and bladder carcinoma. 29 Down-regulation of APM components may or may not be associated with decreased transcription of HLA class I heavy chain and b2-microglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…3 A frequent finding is the downregulation of expression or complete loss of HLA alleles on tumors. [4][5][6] Likewise, tumor cells can become deficient in peptide antigen delivery and processing through loss of TAP transporters, which are responsible for loading peptides onto MHC class I complexes in the ER 7 and by exchanging proteasome subunits. 8 Although certain vaccination approaches with tumor-associated peptides or proteins can induce tumor-specific T-cell responses in patients, the efficacy and response rate of such treatments is not very satisfactory and far from clinic routine.…”
mentioning
confidence: 99%
“…As the anti-tumour cytotoxic T lymphocyte (CTL) response is induced by the recognition of immunogenic epitopes that are presented on various types of HLA class I molecules on the tumour (Marincola et al, 2000;Tangri et al, 2001;Cabrera et al, 2007;Nagorsen and Thiel, 2008), it is important to evaluate the status of HLA class I molecules on tumour cells. It has been reported that the downregulation of HLA class I molecules in the tumour commonly occurred, and the defect of HLA class I molecules is significantly related to patient survival in several malignancies including ESCC (Hosch et al, 1997a;Kageshita et al, 1999;Ryschich et al, 2005;Vitale et al, 2005;Ogino et al, 2006;Ramnath et al, 2006;Speetjens et al, 2008;Ueda et al, 2008). Moreover, it is well known that the downregulation of HLA class I on the tumour allows it to evade CTL-mediated anti-tumour immunity, leading to variant cancer cells that arise from the parent tumour during tumour progression at both primary and metastatic sites.…”
mentioning
confidence: 99%